Anatomical Landmarks and Measurements of Craniofacial Structures: A Micro-CT Analysis - Parmasari, Wahyuni Dyah; Ardani, I Gusti Aju Wahju; Narmada, Ida Bagus; Nugraha, Alexander Patera; Putra, Ramadhan Hardani; Latief, Fourier Dzar Eljabbar; Bahraini, Fahrisah Nurfadeliah (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
In this study, an adult rat's calvaria was used to examine craniofacial anatomical landmarks of maxilla and mandible using Micro-Computed Tomography (micro-CT) as the marker of craniofacial growth and development in rat. It is used to assist research, translating landmark points for diagnosis. Landmarks on the rat’s calvaria were determined to set the measurements of two specified points. One of the ways to validate craniofacial growth and development is to look at the differences between craniofacial before and after a specified period or treatment. With micro-CT analysis, the researchers are more precise in determining the difficult points in the cranium.The sample analysis was carried out and measured by DataViewer version 1.6.0.0 64-bit Application. CTVox version-3.3.1 64-bit is used to display 3D visuals. Reconstruction results after adjusting the data range were 30-255 (the color range 0-255). The machine used was Bruker SkyScan-1173 High Energy Micro-CT. Findings anatomical landmarks for the examples, the maxilla determined I for the point on premaxilla between jawbone and lingual surface of upper incisors. In the mandible, I’ for the most anterior edge of the alveolar bone on the convexity of the lower incisor. The unevenness of the cranium made manual measurements difficult and not possible. However, this micro-CT method makes the landmark point determination more detailed and dependable. This makes geometric measurements of craniofacial more reliable. Micro-CT analysis is a more dependable method to determine anatomical landmarks and measure craniofacial structures as the marker of craniofacial growth and development in rat.